Progressive Industrial Policy in Europe (Taylor & Francis, 2026)
Amid accelerating global warming, the digital revolution and rising geopolitical tensions, industrial policy has taken centre-stage in EU policymaking. Consequently, initiatives such as the Green Deal Industrial Plan, the CHIPS & Science Act, the Important Projects of Common European Interest (IPCEIs) and the InvestAI initiative have been developed or proposed recently. Meanwhile, by reintroducing competitiveness and security as primary objectives for industrial policy, European policymakers appear to backtrack on the social and environmental agenda, while not effectively addressing critical governance deficits and financing gaps. European industrial policy is thus at a critical juncture, and its strategic trajectory is currently under discussion. The volume intervenes into current industrial policy debates from a critical perspective. Achieving sustainable, inclusive and effective industrial policy depends on embracing a progressive approach that prioritises broad stakeholder engagement, effective governance and accelerated implementation, instead of a push for rearmament and geopolitical competition. Progressive Industrial Policy in Europe serves as a key reference for scholars and students in a diverse range of academic disciplines. The volume is also intended for researchers active at trade unions, think tanks and NGOs, along with policymakers and specialised civil servants at supranational, national and local levels. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-NonCommercial-NoDerivatives (CC-BY-NC-ND) 4.0 International license.